Da unidade interna da epistemologia de Wilhelm Dilthey - Lourenço, Luis Eduardo Morimatsu (2022)
The currently study intends to reconstruct the main points of Wilhelm Dilthey's epistemological project in the 19th century. From this reconstruction, we will argue that it is possible to grasp the internal unity of Dilthey's project, which would be guaranteed by two foundations: a theory of experience and a theory of categories. Moreover, we will also argue that once these two foundations have been analyzed, one could better understand his famous methodological distinction between the sciences of nature and the human and social sciences